altri canoni / canoni altri pluralismo e studi letterari - De Zordo, Ornella; FANTACCINI, Fiorenzo (Biblioteca di Studi di Filologia Moderna, 2011)
The concept of the literary canon is one of the most debated and controversial in the western intellectual tradition. This book offers ten contributions by Italian scholars of Anglo-American culture addressing the way in which the concept of the literary canon holds out against areas traditionally considered as external or extraneous to it. The essays range over different topics: the etymological analysis of the term "canon"; the relations between canon and performativity; paraliterature - a universe populated by non-hierarchic genres; the relations between post-colonial literature and the canon; postmodern biofiction; studies on translation and finally gay and lesbian literature. The book ends with a meditation on the innovations wrought on the Anglo-American canon by the virtual world of Internet and with a reading proposal originating from a different area of literary studies. Taken as a whole, the intention of the book is to pave the way to democratisation and pluralism in literary studies, going beyond the limitations set by the traditional scale of values of the "western canon". It proposes a frequentation of the geographical and cultural borderlines and hence of the areas of resistance that such borderlines pose to the dominant conceptual hierarchies within and around us, enabling us to glimpse an original future for literature and for western culture in a broader sense.